Dissecting convergence: occupation rates, structural changes, and sectoral factor reallocations behind regional growth - Carlos Azzoni; Raul Silveira-Neto (European Regional Science Association (ERSA), 2001)
Most studies on convergence analyze the dynamics of per capita income, instead of the theoretically more appropriate product per worker (PPW). This study deals with the latter, providing information on the dynamics of regional product, net of the regional dynamics of occupation rates. It also assesses the contribution of different sectors to regional growth dynamics, stressing the role of sectoral structure changes in the regional dynamics of PPW, bringing some ideas from economic development literature into the convergence debate. Finally, the study analyzes the possible influence of factor reallocation among sectors to regional growth. Empirical evidence on the case of Brazilian states in the period 1981-1997 is offered.
Keywords: 330